[OA215] Impact of tube potential and beam width of CBCT scans on size-specific dose estimate (SSDE) factors. (August 2018) - Abuhaimed, Abdullah; Martin, Colin; Demirkaya, Omer
Abstract : Purpose: Investigate the influence of tube potential and beam width of CBCT scans on the correction factors (fsize ) used to assess size-specific dose estimate (SSDE). Methods: A validated Monte Carlo model for an on-board-imager (OBI) kV system was involved. Four tube potentials (80, 100, 120, 140) kV and four beam widths along the z-axis (80, 160, 240, 320) mm were investigated. Head and body scan protocols employed in the clinic with full and half bowtie filters, respectively, were used to assess fsize values in water phantoms with a length of 900 mm and a diameter ranging from 10 to 24 cm for head and 24 to 50 cm for body. Absorbed dose in water was estimated at center and periphery of the phantoms, from which weighted values (ADw ) (1/3 center and 2/3 periphery) were obtained. Since the conventional CTDIvol is not suitable for CBCT, the modified form of CTDI that was extended for CBCT dosimetry was used. It is based on assessing CTDI100 of a reference thin beam within the standard CTDI PMMA phantoms, and applying a correction factor based on free-in-air measurements for the reference beam and the wide beam of interest. Therefore, ADw values were normalized with respect to those of the modified CTDI, and the results were compared to those reported by AAPM TG–204 for CT scans. Results: fsize Values were influenced by width of the scan beam by 2–36% for head and 4–42% for body for the tube potentials studied. Variations in the fsize values resulting from different tube potentials were within ±18% for head and ±16% for body. Generally, the variations were enhanced by increasing the width of the scan beam, tube potential, and diameter of the water phantom. For 120 kV, fsize values of head and body varied by ±25% and ±43%, respectively, from those reported by the AAPM. Conclusions: Beam width of a CBCT scan was found to play a significant role in determining fsize values, and the influence increased for wider beams. Specific fsize values may be derived for CBCT scans different from multi-detector CT ones.